Otimização econômica de redes de distribuição de água em ambiente SIG - COSTA, Kleber Elias (2010)
In the last decades there has been an increasing interest in the optimization of water distribution networks projects (LANSEY, 2006). This is the result of an urgent need to save public money, and especially to make good use of water, this precious resource, scarce and inaccessible in many parts of the world. In this scenario, many optimization routines of water distribution networks have been used. One of these routines is the Granados Method, which was developed by Alfredo Granados, in 1990, and provides the minimum cost of a water distribution network, considering the change in the price of the pipes according to their types, classes and diameters. One of the modern tools that have being used as a support to the project of water distribution networks is the free software EPANET, which is a simulator of the behavior and quality of the water, widely used in distribution systems under pressure. Geoprocessing, in turn, has been used in many areas, including the development of networks, be they water, sewer, electricity, transport, telephone etc. The ArcView GIS is a software that is widely accepted by researchers and designers worldwide. The EPANET integrated with the software ArcView GIS can work together through the installation of the software DC Water. Thus, we can run the hydraulic simulator EPANET within the environment of ArcView GIS. Through this work, we developed a computational routine based on Granados optimization method, within the geoprocessing software ArcView GIS, integrated with EPANET through the DC Water. This routine allows, in an automated way to carry out several simulations of diameters implementation, analyzing the energy losses and the resulting pressure on knots, in order to contribute to the production of an optimized water supply network.